THE COUCH TURNTABLE TECHNIQUE IN LATERAL HEAD AND NECK IRRADIATION : A HOMOGENEITY OF DOSE DISTRIBUTION AND DOSE DELIVERED TO ADJACENT NORMAL TISSUES - TUNTIPUMIAMORN, Lalida; POLWATSATIAN, Vinai; KARNJANATHITIWORN, Udomsak (The ASEAN Journal of Radiology, 2023)
The objective of this study was to investigate for the uniformity of dose distribution and also the dose delivered to adjacent normal tissues compared between the Straight Field and the Couch Turntable technique in Cobalt-60 lateral head and neck irradiation. Doses were measured in an anthropomorphic wax phantom with TLD-100 dosimeters. Measurements were performed three times in each technique and the analysis was done by normalizing doses at each measuring point as a percentage of dose at the reference point. From the study, the doses distribution homogeneities are satisfied in both techniques. The average doses were 95.38+7.41 in the technique of Straight Field and 95.07+8.15 in the technique of Couch Turntable. In the matter of doses to adjacent normal organs, it is likely that the use of Couch Turntable provided higher doses than the technique of Straight Field. Measured doses at brain tissue (under shielding blocks) in the technique of Couch Turntable was 45.74+11.83, at buccal mucosa was 65.18+5.24 and at lens was 5.05+14.8 respectively. Compared to the technique of straight field, the average measured dose were 30.39+5.39 at brain, 56.10+6.56 at buccal mucosa, and 4.88+16.7 at lens. It is clearly shown that uses of the Couch Turntable to solve for the beam divergence do not affect on the dose distribution homogeneity when compared to the technique of Straight Field. But higher doses at adjacent normal tissues, especially at brain should be aware of.